Typology and Provenance of Early Roman Cooking Ware from the Residential Quarter of Nea Paphos (Cyprus) - Miziołek, Monika; Marzec, Edyta (Études et Travaux, 2024)
This paper concerns the early Roman cooking ware uncovered at Maloutena – the residential quarter of Nea Paphos, Cyprus. All registered diagnostic fragments were subjected to macroscopic, typological and quantitative examinations, and a selection of samples was analysed with petrographic and elemental analyses. The results show that locally produced cooking ware is predominant and diverse in terms of typology. Among imports, pottery from north-western Cyprus, Asia Minor, Italy, and Africa is identified, but it constitutes a small part of the assemblage. These indicate that Nea Paphos participated in broader networks of goods circulation, but at the same time, the city’s inhabitants preferred locally produced cooking ware.